Analisis Pengaruh Dynamic Capabilities Terhadap Kinerja UMKM Ditengah Fluktuasi Pasar: Studi Kasus Pada Joesa Salon - Fitri Hasnawati, Naila; Marlina, Jeni; F Sanjaya, Vicky (POLITEKNIK LP3I, 2025)
This study aims to understand the influence of dynamic capabilities on the adaptive performance of salon MSMEs in facing market fluctuations. Using a qualitative approach, the study explores the experiences of salon owners and managers in applying detecting, seizing, and reconfiguring capabilities as adaptation strategies. Information was collected through in-depth interviews, observations, and documentation, then analyzed using thematic analysis techniques. The results show that detecting capabilities enable salons to recognize changes in beauty trends, customer preferences, and competitive dynamics. Seizing capabilities help salons capitalize on opportunities through service updates, product innovation, and advanced marketing strategies. Meanwhile, reconfiguring capabilities are reflected in resource adjustments, employee training, technology use, and operational process improvements. The three components of dynamic capabilities were found to contribute significantly to the adaptive performance of salons, particularly in maintaining service relevance and increasing competitiveness. Internal factors such as visionary leadership, innovative culture, and human resource competencies also strengthen the effectiveness of the application of dynamic capabilities. This study emphasizes the importance of continuous adaptation capabilities for SME salons in order to survive and thrive amid rapid market changes.